2018
DOI: 10.1101/509042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loud music and the specific sound stress open the blood-brain barrier: new fundamental, biomedical, and social aspects

Abstract: The blood-brain barrier (BBB) poses a significant challenge for drug brain delivery. The limitation of our knowledge about the nature of BBB explains the slow progress in the therapy of brain diseases and absence of methods for drug brain delivery in the clinical practice.Here we show that BBB opens for low/high weight molecules and nanocarriers after exposure of loud music/sound of 90 dB and 100 dB (regardless its frequency) as being easily produced by MP3/MP4 players, kitchen appliances, loudspeakers at conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Studies varied between intensity and exposure time to music, sound, or noise. Semyachkina-Glushkovskaya et al [ 20 ] showed that music/sound exposure had different effects at 70 dB vs. 90 and 100 dB and at 1-h durations vs. 4- and 24-h durations. The lower stimulus had a similar effect on BBB permeability as the control group (no music/sound stimulus), whereas both 90- and 100-dB exposure increased BBB permeability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies varied between intensity and exposure time to music, sound, or noise. Semyachkina-Glushkovskaya et al [ 20 ] showed that music/sound exposure had different effects at 70 dB vs. 90 and 100 dB and at 1-h durations vs. 4- and 24-h durations. The lower stimulus had a similar effect on BBB permeability as the control group (no music/sound stimulus), whereas both 90- and 100-dB exposure increased BBB permeability.…”
Section: Resultsmentioning
confidence: 99%
“…The studies mentioned above showed that music affects the function and health of the body and brain, autonomic and cognitive function, and neuronal function and health, often positively. In addition, there is preliminary evidence regarding the effects of music/sound on the activity of the glymphatic system [ 19 , 20 ]. Several studies have also researched the effects of ultrasound on glymphatic clearance [ 21 , 22 , 23 ].…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…To get the training SNR examples, we used EEG signals before (EEG1) and after (EEG2) artificially increased permeability of the BBB [55]. During the training, the fragments of SNR for the rat after music stimulation were marked as the expected response "1" (i.e.…”
Section: Ann Based Methodsmentioning
confidence: 99%
“…The further equipment details can be found in [40], while the extended discussion of the method validation and the results obtained can be found in [42,43].…”
Section: Experimental Datamentioning
confidence: 99%